EFFECT OF GROWTH REGULATORS ON SEED YIELD AND ITS COMPONENTS OF TWO ALFALFA CULTIVARS - & Al-Beiruty, Khrbeet (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field study was conducted at the experimental farm, College of Agriculture, Abu-Ghraib, Baghdad, Iraq during the period from mid. of March 2012 to mid. of July 2014 to investigate the effects of plant growth regulators and foliar application stages on seed yield and it’s components of two alfalfa cultivars. Layout of the experiment was R.C.B.D. arranged in split-split plot with three replications. Cultivars (local and hamedan) were assigned as a main plot and foliar application stages (vegetative growth, flower buds emergence, 50% flowering and 80% flowering) were assigned as sub-plots, while growth regulators (Alar, Ethephon, Naphthalene acetic acid (NAA) and control treatment) were assigned in the sub-sub-plots. Result showed that there were no significant differences between local cult. and c.v Hamadan in seed yield and it’s components except 1000 seed weight. Foliar application of growth regulators at flower buds emergence significantly increased No. of racemes per stem and No. of seed per pod, therefore it produced highest seed yield (450 kg/ha) as a mean of two seasons. In 1st seed crop, there were significant interaction between cultivars and foliar application stages on seed yield since local cult. gave highest seed yield (479.6 Kg/ha) when it spraying at flower buds emergence stage with an increasment 14.5% compare with hamedan C.V. foliar application alar significantly increased No. of seeds per pod and seed yield in both season , but it was not significantly different than NAA. Since, increasment in seed yield compare with ethephon and control treatment reach (25.4, 18.3), (18.8, 17.7) in 1st and 2nd seed crop respectively. as average for two seasons, higher seed yield (565 Kg/ha) can be obtained from sowing local cultivar and foliar application of alar when the stand reaches at flower buds emergence stage.